2019
DOI: 10.1002/1878-0261.12562
|View full text |Cite
|
Sign up to set email alerts
|

miR‐367 as a therapeutic target in stem‐like cells from embryonal central nervous system tumors

Abstract: Aberrant expression of the pluripotency factor OCT4A in embryonal tumors of the central nervous system (CNS) is a key factor that contributes to tumor aggressiveness and correlates with poor patient survival. OCT4A overexpression has been shown to up‐regulate miR‐367, a microRNA (miRNA) that regulates pluripotency in embryonic stem cells and stem‐like aggressive traits in cancer cells. Here, we show that (a) miR‐367 is carried in microvesicles derived from embryonal CNS tumor cells expressing OCT4A; and (b) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…At the same time, MIR518B was up-regulated and reported to manifest tumor suppressive properties in glioblastoma [ 75 , 76 ]. Interestingly, MIR367 was recently found to function as tumor promoting miRNA, since its inhibition attenuates tumor aggressiveness and proliferation in embryonal tumors [ 77 , 78 , 79 ]. On the other hand, MIR613 was reported to act as a tumor suppressor, inhibiting glioma progression [ 80 ], while we found it up-regulated in the majority of the CNS tumors.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, MIR518B was up-regulated and reported to manifest tumor suppressive properties in glioblastoma [ 75 , 76 ]. Interestingly, MIR367 was recently found to function as tumor promoting miRNA, since its inhibition attenuates tumor aggressiveness and proliferation in embryonal tumors [ 77 , 78 , 79 ]. On the other hand, MIR613 was reported to act as a tumor suppressor, inhibiting glioma progression [ 80 ], while we found it up-regulated in the majority of the CNS tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-367-3p reversed the induction of apoptosis by sevoflurane, potentially rendering neurons in the hippocampus resistant to sevoflurane. A study by Kaid et al ( 31 ) demonstrated that miR-367-3p exhibited certain stem cell-enhancing characteristics, and improved the pluripotency of embryonic stem cells and the invasiveness of cancer-like stem cells. Wang et al ( 32 ) revealed that treatment with adriamycin induced apoptosis of osteosarcoma cells with upregulation of miR-367-3p.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Kaid and her colleagues discovered that miR-367 may be a medical target, which can be used as a marker in aggressive embryonal central nervous system tumor and facilitates prognosis and early diagnosis. [ 13 ] Furthermore, miR-367-3p expression levels are closely correlated with International Federation of Gynecology and Obstetrics (FIGO) stage and lymph node metastasis, and high expression of miR-367-3p allows to a high survival rate, oppresses cancer cell metastasis, and quenches the malignant behaviors of tumor in endometrial cancer. [ 14 ] Although miR-367 is reported to regulate the pathological development in different human cancers, researches about the functions of miR-367 in BC progression need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…As a key member of the miR-302/367 cluster, miR-367 can play a role in a number of cancers as it prevents cell senescence and death, maintains proliferation signal activation, sabotages growth inhibitors, and modulates cellular biological activities as well as angiogenesis [12] . Kaid and her colleagues discovered that miR-367 may be a medical target, which can be used as a marker in aggressive embryonal central nervous system tumor and facilitates prognosis and early diagnosis [13] . Furthermore, miR-367-3p expression levels are closely correlated with International Federation of Gynecology and Obstetrics (FIGO) stage and lymph node metastasis, and high expression of miR-367-3p allows to a high survival rate, oppresses cancer cell metastasis, and quenches the malignant behaviors of tumor in endometrial cancer [14] .…”
Section: Introductionmentioning
confidence: 99%